Localization, structure and polymorphism of two paralogous Xenopus laevis mitochondrial malate dehydrogenase genes - Tlapáková, Tereza; Krylov, Vladimír; Mácha, Jaroslav (Chromosome research, 2005)
Two paralogous mitochondrial malate dehydrogenase 2 (Mdh2) genes of Xenopus laevis have been cloned and sequenced, revealing 95% identity. Fluorescence in-situ hybridization (FISH) combined with tyramide amplification discriminates both genes; Mdh2a was localized into chromosome q3 and Mdh2b into chromosome q8. One kb cDNA probes detect both genes with 85% accuracy. The remaining signals were on the paralogous counterpart. Introns interrupt coding sequences at the same nucleotide as defined for mouse. Restriction polymorphism has been detected in the first intron of Mdh2a, while the individual variability in intron 6 of Mdh2b gene is represented by an insertion of incomplete retrotransposon L1Xl. Rates of nucleotide substitutions indicate that both genes are under similar evolutionary constraints. X. laevis Mdh2 genes can be used as markers for physical mapping and linkage analysis.
Keywords: financování organizované; Animals; Base Sequence; sekvenční homologie aminokyselin; exprimované sekvenční adresy; karyotypizace; Mitochondria; Sequence Homology, Amino Acid; techniky amplifikace nukleových kyselin; mapování chromozomů; sekvence aminokyselin; introny; Chromosome Mapping; Karyotyping; duplicitní geny; Retroelements; Molecular Sequence Data; Introns; Amino Acid Sequence; Genetic Variation; mitochondrie; Financing, Organized; Xenopus laevis; molekulární sekvence - údaje; Chromosomes; retroelementy; Cloning, Molecular; konzervovaná sekvence; Malate Dehydrogenase; polymorfismus genetický; Nucleic Acid Amplification Techniques; sekvence nukleotidů; hybridizace in situ fluorescenční; klonování DNA; Expressed Sequence Tags; malátdehydrogenasa; zvířata; In Situ Hybridization, Fluorescence; chromozomy; genetická variace; Polymorphism, Genetic; Genes, Duplicate; Conserved Sequence